Optic neuropathy as a presenting feature of vitamin B-12 deficiency: A systematic review of literature and a case report (2020)
Introduction: Vitamin B12 (VitB12) deficiency rarely manifests with visual symptoms. Optic nerve damage in VitB12 deficiency is thought to be via degeneration. However, optic neuritis, though infrequent, has been reported secondary to VitB12 deficiency. Material and methods: We conducted a systematic review of all the reported cases of VitB12 deficiency with optic nerve involvement in Pubmed, Cochrane, and Google Scholar any date up to September 6, 2020. We have discussed the findings and compiled the available information on ophthalmological manifestations of VitB12 deficiency. We aim to provide a unified knowledge about the evidence related to types of optic neuropathies reported to date secondary to VitB12 deficiency. We also present a case of bilateral optic neuritis secondary to VitB12 deficiency. Presentation of case: We present a 29-year-old previously healthy male with progressive, painful, bilateral, but asymmetric visual deterioration for forty-five days. A detailed history, examination, and laboratory workup were carried out. He was diagnosed as having optic neuritis secondary to VitB12 deficiency. He showed partial improvement with the replacement of VitB12. Conclusion: We suggest promptly identifying and replacing VitB12 in patients with optic neuritis with proven VitB12 deficiency to prevent permanent damage to the optic nerve. Patients with VitB12 deficiency should have a baseline fundoscopic exam to rule out subclinical optic nerve damage. Moreover, patients who present with visual disturbances should be screened for VitB12 deficiency, especially the vegan population.